2012
DOI: 10.3174/ajnr.a3264
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Cerebral Extraventricular Neurocytoma: A Report of 9 Cases

Abstract: SUMMARY: Extraventricular neurocytoma is a rare entity, most frequently occurring in brain parenchyma outside the ventricular system. The purpose of this study was to characterize the MR imaging findings in a series of 9 patients with EVN verified by results of pathologic examination. All 9 EVNs were solitary and intracranially located. Eight lesions were well demarcated, and 3 showed intratumoral hemorrhage. The solid parts of 7 tumors were primarily isointense on T1-weighted images and heterogeneously enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
(50 reference statements)
0
23
0
4
Order By: Relevance
“…The MRI signal intensity increase caused by the leakage of Gd-DTPA thus serves as an indicator to estimate drug concentration [4, 8, 9, 17]. Most studies have focused on analyzing the effects of FUS exposure parameters such as acoustic pressure amplitude, ultrasound frequency, pulse length, pulse repetition frequency, exposure duration, and microbubble dose on BBB opening [5, 1823].…”
Section: Introductionmentioning
confidence: 99%
“…The MRI signal intensity increase caused by the leakage of Gd-DTPA thus serves as an indicator to estimate drug concentration [4, 8, 9, 17]. Most studies have focused on analyzing the effects of FUS exposure parameters such as acoustic pressure amplitude, ultrasound frequency, pulse length, pulse repetition frequency, exposure duration, and microbubble dose on BBB opening [5, 1823].…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Giangaspero et al ( 5 ) reported the first case of a tumor that mimicked CNC, but was located in an extraventricular region. In 2007, these tumors were classified by the WHO as a novel brain tumor entity ( 4 ), and the incidence of EVN remains extremely rare, with Liu et al ( 6 ) reporting a worldwide incidence of only 0.13%. The development of CNC appears to have no significant gender predilection; however, the literature indicates that EVN has a slight female predominance and a median patient age of 38 years (range, 5–76 years) ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…On imaging analysis, EVNs may appear as well-circumscribed, round or multilobular, hypodense or isodense masses, which are homogeneously-enhanced with contrast medium, as observed in the present case. Liu et al ( 6 ) reported that cystic degeneration was observed in 6 out of 9 (66%) EVN cases, with calcification in 34% and perilesional edema in 44%, whilst Patil et al ( 11 ) reported that cystic degeneration was present in 71% of 9 cases and perifocal edema in 57%. MRI may exhibit an isointense or slightly hyperintense signal compared with the cortex on T1- and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Extraventricular Neurocytoma (EVN) is a rare primary tumor of Central Nervous System (CNS) [1], -grade II according to World Health Organization (WHO) classifi cation [2,3], that commonly manifests in young adults with partial seizures, headache or focal neurological defi cits [4][5][6]. Conversely, Central Neurocytoma tipically presents with signs and symptoms of intracranial increased pressure and hydrocephalus [6].…”
Section: Introductionmentioning
confidence: 99%
“…CNS) -incidence about 0,13%[1], distinct hystological entity from the classic Central Neurocytoma; this latter one is typically located in the anterior portion of third and lateral ventricles, while EVN can be usually found in frontal and parietal lobes[7]. 2007 World Health Organization (WHO) classifi cation fi rst introduced EVN as a defi ned primary lesion of the CNS, included in the group of "neuronal and mixed…”
mentioning
confidence: 99%